Optical Properties and Characterization of Prepared Sn-Doped PbSe Thin Film - M. R. Khanlary; E. Salavati (Advances in Condensed Matter Physics)
Physical vapor deposition of tin-doped lead selenide (Sn/PbSe) thin films on SiO2 glass is described. Interaction of high-energy Ar+ ions bombardment on the doped PbSe films is discussed by XRD analysis. The improvement of optical band gap of Sn/PbSe films irradiated by different doses of irradiation was studied using transmission spectroscopy.